Big words for little astronauts : the stellar dictionary every space explorer needs - Gerry, Lisa M. (National Geographic kids., 2024)
"From sounding out big words--like "propulsion," "meteorite," and even "extraterrestrial"!--to simplifying big concepts--like gravity and atmosphere--this star-studded dictionary is the perfect launching pad for kids who absolutely love all things space. It features more than 50 wow-worthy words, each with a definition and phonetic pronunciation, helping your little explorer sound like an expert in no time. Cosmic illustrations, fascinating photos, and a lovable character, Grover the rover, will keep every space-loving kid engaged and wanting more. And, with the seal of approval from Kathryn Sullivan--former astronaut and the first American woman to walk in space for NASA--readers can trust that our content is coming straight from the source."--